Vitrine tecnológica da Universidade Federal de Roraima: uma ferramenta de aproximação na relação universidade-empresa - Tavares, Aline Barros (2019)
The knowledge generated by the universities is a determining factor for innovation and competitiveness of companies. The technical literature, however, addresses the limitations of this relationship. This study focuses on the deficient academy-company interaction and proposes the creation of a technological showcase as a tool to approach this relationship. The data were collected through semi-structured interviews with 21 UFRR research group leaders registered in the CNPq Research Groups Directory. The survey results highlight the need for effective implementation of actions by the NIT and provide the basis for building the technology showcase with the exposure of protected technologies and technological competences of the researchers, on the supply side, and with demands from companies for their technological solutions, on the demand side.